To solve the equation \( 5(2x + 2) - 7x = 3x + 6 \), we first simplify it step by step.
-
Distribute the 5 on the left side: \[ 5(2x) + 5(2) - 7x = 3x + 6 \] \[ 10x + 10 - 7x = 3x + 6 \]
-
Combine like terms on the left side: \[ (10x - 7x) + 10 = 3x + 6 \] \[ 3x + 10 = 3x + 6 \]
-
Subtract \(3x\) from both sides: \[ 10 = 6 \]
At this point, we notice that \(10 = 6\) is a false statement. This indicates that the original equation has no solutions.
Therefore, the correct response is: The equation has no solution.